Acmeological technology of forecasting individual professional-oriented trajectories of students' personality development - E. F. Zeer; L. N. Stepanova (Russian State Vocational Pedagogical University, 2023)
Introduction. In the conditions of deep transformations of modern society and labour market, the problem of revising qualification requirements for the content and level of training of professional personnel is being actualised. The main task of university education is to modernise curricula in order to form an independent subject of the educational process. The formation of such a specialist is possible through the use of individual scenarios for the educational and professional development of the student's personality, both in basic and additional, including distance education throughout his/herprofessional biography. Only, in this case, the graduate will be ready to meet with the social and professional innovations of the future.   Aim. The aim of the study is to theoretically substantiate, develop and test the acmeological technology of forecasting the individual professional-oriented trajectory of student personality development in the educational process of the university.   Methodology and research methods. At the theoretical level, the article substantiates the concept of "individual professional-oriented trajectory of personality development", develops the authors' acmeological technology for predicting individual scenarios of educational and professional development of a student's personality. The following tools and methods were applied: analysis, comparison, generalisation, authors' interpretation of psychological and pedagogical literary sources in the field of individualisation and personalisation of education, construction of individual trajectories of educational and professional development of the student's personality, and technological approach in education. The method of structural and functional modelling of acmeological technology was applied. The essence of the abovementioned method is to identify and describe the fundamental structural components and stages of technology that ensure the achievement of the desired result, identify the relationships between them and establish their functional characteristics. The experimental work included the initial diagnosis of a total sample of 180 first-year students of the Faculty of Psychology. The initial diagnosis was conducted before the implementation of the elective programme. As diagnostic tools for studying individual educational and professional trajectories, the following were used: the authors' questionnaire "Individual Trajectories of Educational and ProfessionalDevelopment of Students" by E. F. Zeer, L. N. Stepanova; "Modified Questionnaire for the Diagnosis of Self-Actualisation of Personality" by A. V. Lazukin in the adaptation of N. F. Kalin; methodology "Investigation the Motivation of Studying at a University" by T. I. Ilyina; methodology "Meaning-Life Orientations" by D. A. Leontiev. To diagnose soft skills of students, a set of techniques was employed: "Coping Behaviour in Stressful Situations CISS" by S. Norman in adaptation by T. L. Kryukova; the test "Ability to Predict" by L. A. Regush; the methodology "Research of the Attitude of Personality to Innovation" by N. M. Lebedeva, A. N. Tatarenko; test "My Information Culture" by N. I. Gendin; self-test "Readiness for Self-Development" by V. V. Pavlov, T. A. Ratanova, N. F. Flakhta. Statistical data processing was carried out using the standardised IBM SPSS Statistics 17.0 software package.   Results and scientific novelty. The concept of "individual professional-oriented trajectory of student's personality development" is clarified; its structural components are highlighted: value-motivational cognitive, operational-activity and reflexive. The logical-evolutionary, system-dynamic, project-based and personal approaches of individual scenarios forecasting of educational and professional development of students developed by E. F. Zeer are presented. The following principles of forecasting the academic and professional development of the individual are substantiated: the principle of personal co-development, education and professional development; the principle of interaction of individual, personal and professional development; the principle of socio-professional mobility; the principle of alternative and multivariate forecasting of the professional future. The intrapersonal and environmental predictors of forecasting the individual educational and professional trajectory of student development during the period of professional training are determined, among which special importance is given to the educational environment of the university and its characteristics such as intensity, psychological comfort, democracy and openness. The acmeological technology of individual scenarios forecasting of educational and professional development of students has been scientifically substantiated, developed and tested. The results of testing confirm its effectiveness and the possibility of use in secondary and higher educational institutions. At the same time, the presented technology can be considered as a tool for improving students' soft skills: innovative potential of the individual, willingness to solve problems and self-development, meaningfulness of life, development of a personal goal-setting system and time management. The obtained results expand the ideas existing in psychological science about the ways of individualisation of educational and professional personality development.   Practical significance. The research results can be used in educational institutions of higher and secondary vocational education by psychologists, tutors, teachers who provide psychological and pedagogical support to students. Forecasting individual scenarios of educational and professional development promotes conscious entry into the profession and awareness of the personal meanings of the education received, which is of particular value as a prevention of negative scenarios of professional development of the individual in the future.